On advancing of glaciers due to activity of the Klyuchevskaya Sopka volcano (Kamchatka) - M. D. Dokukin; I. B. Seynova; E. A. Savernyuk; S. S. Chernomorets (Лëд и снег, 2017)
New data on continuing advance of the Kamchatka glaciers Erman, Vlodavets, Sopochny, Schmidt, and Bogdanovich were obtained as a result of analysis of aerospace information taken at different times. Glacier Erman advances during the past 70  years (1945–2016). Over the period from 1949 to 2016, its area increased by 4.7 km2 and the length – by 3.3 km (from 18.2 to 21.5 km). The highest speed of advancing had been estimated for the Schmidt glacier, in 2007–2013 it exceeded 100 m/year. We had identified a new isolated glacier between glaciers Erman and Schmidt, named as the Obvalny (the «Avalanche») glacier, since in 1945 this glacier was buried under volcanic-avalanche deposits resulted from the Klyuchevskaya volcano eruption. In 1975–2016, the Obvalny glacier advanced over a distance of about 1700 m. Also, we had found more 30 ice-rock massifs («wandering glaciers») on slopes of the Klyuchevskaya volcano. Their contours looked like drops or tongues, and some of them advanced in the frontal zone. From 2002 to 2016, the «wandering glacier» in the upper reaches of river Glubokaya (eastern sector of the volcano) advanced for 740 m (55 m/year). Advancing of glaciers here is a consequence of lateral and terminal eruptions of the Klyuchevskaya volcano in XX and XXI centuries. Erman Glacier, glacier advance, Klyuchevskaya volcano, lateral eruption, space images, volcanic and rock avalanche deposits, «wandering glaciers».